Piper Reed, Navy brat [compact disc, unabridged] - Holt, Kimberly Willis (Random House/Listening Library, 2007)
Piper is sad about leaving her home and friends behind when her father, a Navy aircraft mechanic, is transferred yet again, but with help from her often-annoying sisters and a surprise from their parents, she finds happiness in their new home in Pensacola, Florida.